Consideration of the degree of increase in urine metadrenalines provides superior specificity in the diagnosis of phaeochromocytoma than additional urine catecholamine measurement. (January 2013) - Scargill, J J; Reed, P; Kane, J
Background: Measurement of fractionated plasma or urine metadrenalines is the recommended screening test in the diagnosis of phaeochromocytoma, with clinical cut-offs geared towards diagnostic sensitivity. Current practice at Salford Royal Hospital is to add urine catecholamines onto samples with raised urine metadrenalines, with the aim of adding specificity to a diagnosis of phaeochromocytoma. Methods: This practice was reviewed by identifying a series of patients with raised urine metadrenalines who had catecholamines reflectively added. A total of 358 samples were identified from 242 patients, of which 228 had urine catecholamines measured. Results: A diagnosis of 'phaeochromocytoma' (n = 41) or 'no phaeochromocytoma' (n = 90) was obtained in 131 of 228 patients, giving raised urine metadrenalines a positive predictive value for phaeochromocytoma of 31%. The finding of increased urine catecholamines in samples with raised urine metadrenalines increased specificity for phaeochromocytoma to 70%. However, 95% diagnostic specificity for phaeochromocytoma could be achieved by the introduction of a second cut-off for urine metadrenalines geared towards maximizing specificity. Conclusions: Consideration of the degree of increase in urine metadrenalines is a superior method of determining the likelihood of phaeochromocytoma than measurement of urine catecholamines.